EFEKTIVITAS MINYAK ZAITUN DALAM PENCEGAHAN ULKUS DEKUBITUS PADA PASIEN TIRAH BARING DENGAN MASALAH KEPERAWATAN RISIKO LUKA TEKAN DI RUANG MICU: STUDI KASUS - Taqiuddin, Muhammad Hafidh; Maria Komariah; Rian Hara Permana (Universitas Islam Negeri Alauddin Makassar, 2024)
Decubitus ulcers or what can be called bed sores are wounds that occur due to the skin of certain parts of the body being pressed for a long period of time due to bed rest. As an effort to prevent decubitus ulcers, skin care is carried out using olive oil as a moisturizer. Methods: The research method used is a case study. The data analysis used in this case study is a nursing process approach model which consists of stages: nursing assessment, analysis of problem formulation and nursing diagnosis, intervention, implementation, evaluation and nursing documentation. The results of the case study after nursing action was carried out in the form of administering olive oil for 3 days as a moisturizer showed that the condition of the skin that was under pressure remained intact, there were no signs of decubitus wounds, and the skin's moisture was maintained. Keywords: Decubitus ulcer, olive oil, pressure sores, bed rest